2017
DOI: 10.5124/jkma.2017.60.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of headache and headache-related disability in children and adolescents

Abstract: Headache is a frequent neurological symptom in children and adolescents. Recurrent headaches have a significant disabling effect, with consequences including school absenteeism, decreased participation in extracurricular activities, and poor academic performance, and are a risk factor for further chronic headaches and other pain syndromes that merit increased attention. The most common types of primary headache in children and adolescents are migraine and tension-type headache (TTH). In a recent survey of Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Headache is a highly common disease among children and adolescents and substantially affects their quality of life [20]. In a study of school-aged children in South Korea, 29.1% of children developed headaches, and approximately 6.7% reported experiencing other types of headache than migraine and tension-type headaches [1].…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a highly common disease among children and adolescents and substantially affects their quality of life [20]. In a study of school-aged children in South Korea, 29.1% of children developed headaches, and approximately 6.7% reported experiencing other types of headache than migraine and tension-type headaches [1].…”
Section: Discussionmentioning
confidence: 99%
“…The most common primary headaches are tension-type headaches and migraines, and studies have shown that tension-type headaches have a higher prevalence, although migraines are more painful and result in more frequent hospital visits [ 11 ]. Repetitive headaches impede academic achievement and/or daily life due to decreased concentration, tardiness, and absence from class [ 9 ].…”
Section: Epidemiology and Characteristicsmentioning
confidence: 99%